Pendampingan Peningkatan Kompetensi Guru dalam Pembelajaran di Kelas Berbasis Praktikum dan Aplikasi STEM Fase F untuk MGMP Fisika Kota Pontianak - Lia Angraeni; Sari, Ira Nofita; Matsun, Matsun; Pramuda, Adi; Hadiati, Soka; Saputri, Dwi Fajar; Boisandi, Boisandi; Hakim Assegaf, Sy. Lukman (Jurnal Inovasi dan Pengabdian kepada Masyarakat (JIPMas), 2025)
The purpose of this community service activity is to provide skills to physics teachers at the Pontianak City Physics MGMP to develop practical-based learning and STEM Phase F applications. The method of implementing PKM is training and mentoring. The stages of implementing PKM consist of stage 1) preparation; stage 2) socialization which includes activities of resource person presentation, discussion, and question and answer; and stage 3) implementation and mentoring, which includes activities; and 4) monitoring and evaluation. This activity succeeded in increasing teachers' insight and skills about the implementation of STEM Phase F in practical-based learning activities. In addition, teachers' skills in compiling STEM-based learning devices also increased. This program succeeded in introducing the application of STEM in practical-based Physics learning in the Lab. The positive response of participants showed motivation to apply STEM and partnerships between universities and schools as the first step to creating an innovative and sustainable learning environment. This PKM produced outputs, namely news in the online mass media of the KALBAR Regional Government